Draupadi’s Disrobing and the Male Gaze: A Feminist Perspective on the Digital Adaptations of the Mahabharata - Suchitra Rani MAHATO; Rajiv BHUSHAN; Maninder KAPOOR (HyperCultura, 2024)
The epic Mahabharata has been adapted into varied genres—theatre, dance, movie, fiction, and television serial. This paper shall focus on two televised versions—one directed by B. R. Chopra and the other by Siddharth Tewary. Interestingly, both are simultaneously available and comparable through the research-friendly digital archive of YouTube and Disney+ Hotstar. The scene of “Draupadi’s disrobing” in the “Game of Dice” episode is the climactic scene of the epic that signals the inevitability of the war of Kurukshetra. Using digital apps, and a close examination of the visual medium this paper shall attempt a comparison of the damning and shaming of Draupadi and her subsequent defiance in the face of male arrogance in the “Game of Dice” episode as presented by B. R. Chopra in 1988 and later by Siddharth Tewary in 2013. It shall identify points of similarity and departure to comment on the diverse messaging strategies employed by the respective directors and argue whether they hammer in different messages. If the message is the same, which director is more potent in establishing it? The paper shall also showcase the power and potential of the visual medium in demonstrating the toxicity of the male gaze in action.